2014
DOI: 10.1186/ar4573
|View full text |Cite
|
Sign up to set email alerts
|

How to build an inducible cartilage-specific transgenic mouse

Abstract: Transgenic mice are used to study the roles of specific proteins in an intact living system. Use of transgenic mice to study processes in cartilage, however, poses some challenges. First of all, many factors involved in cartilage homeostasis and disease are also crucial factors in embryogenesis. Therefore, meddling with these factors often leads to death before birth, and mice who do survive cannot be considered normal. The build-up of cartilage in these mice is altered, making it nearly impossible to truly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…In this scenario, gene knockout occurs upon the physiological activation of the Cre-controlling promoter, which introduces considerable variability. Thus, whereas some promoters — such as the collagen, type II, alpha 1 ( Col2a1 ) promoter 286 — impose an autophagic defect early during differentiation or embryonic development, others — such as the cyclin-dependent kinase inhibitor 2A ( Cdkn2a ) promoter 287 — abolish autophagic proficiency in terminally differentiated cells (in this case, senescent) cells. One of the major issues in this setting is the occurrence of compensatory processes, that is, a general reorganization of cellular functions that partially (if not totally) compensate for the lack of a specific protein.…”
Section: Challenges In Developing Autophagy Modulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this scenario, gene knockout occurs upon the physiological activation of the Cre-controlling promoter, which introduces considerable variability. Thus, whereas some promoters — such as the collagen, type II, alpha 1 ( Col2a1 ) promoter 286 — impose an autophagic defect early during differentiation or embryonic development, others — such as the cyclin-dependent kinase inhibitor 2A ( Cdkn2a ) promoter 287 — abolish autophagic proficiency in terminally differentiated cells (in this case, senescent) cells. One of the major issues in this setting is the occurrence of compensatory processes, that is, a general reorganization of cellular functions that partially (if not totally) compensate for the lack of a specific protein.…”
Section: Challenges In Developing Autophagy Modulatorsmentioning
confidence: 99%
“…For instance, genes that are under the control of the Col2a1 promoter are expressed not only by chondrogenic tissues but also — transiently — in non-chondrogenic tissues, including the notochord, eye, heart, epidermis and discrete areas of the brain 286 . Although this issue is generally marginal, it may have affected — at least to some degree — data interpretation in specific cases.…”
Section: Challenges In Developing Autophagy Modulatorsmentioning
confidence: 99%
“…In this regard, articular cartilage homeostasis during OA is affected by mechanical stress, inflammatory responses, and secondary effects from surrounding tissues. 8 Previous in vitro experiments showed that TXA does not promote chondrocyte function and is cytotoxic to cartilage at concentrations >20 mg·mL -1 . 3,9,47,56 In turn, at concentrations <20 mg·mL -1 , TXA did not affect chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Our data of endogenous expression suggests that articular chondrocytes express approximately 40 times more ACAN than the meniscus cells on a gene level. This suggests that OP1 could have less effect on articular chondrocytes due to the already elevated expression of ACAN and due to complex regulation of this gene in articular cartilage [33]. As a more fibro-cartilagenous tissue, the healthy meniscus may have more ability to respond to OP1 and gain a more cartilage-like ECM composition.…”
Section: Discussionmentioning
confidence: 99%